Investigating the Spiritual Health Status of Surgical Technology and Anesthesia Students at Shahid Sadoughi University of Medical Sciences in 2024 - Amin Ghasemi; Elaheh Marani; Faeze Mazidi Sharafabadi (Health, Spirituality and Medical Ethics)
Background and Objectives: Human health, as one of God’s most wonderful creations, encompasses various dimensions. Spiritual health is one of these dimensions related to the other dimensions. The present study investigates the spiritual health status of students in the Operating Room and Anesthesia Departments at Shahid Sadoughi University of Medical Sciences, Yazd City, Iran, in 2024. Methods: This descriptive-analytical cross-sectional study was conducted on 163 students from the Operating Room and Anesthesia Departments at Shahid Sadoughi University of Medical Sciences, Yazd City, Iran, in 2024, using a census method. The data were collected through a demographic form and the spiritual health questionnaires developed by Paloutzian and Ellison. Meanwhile, the data were then described using descriptive statistics, such as frequency and percentage, and analyzed using inferential statistics, including the t-test and Pearson correlation coefficient, using the SPSS software, version 27. Results: In this study, the mean spiritual health score of students was 90.55±17.43, indicating that the students were at a mean level of spiritual health. No significant relationship was found between gender, marital status, native-ness, field of study, or semester and spiritual health, existential health, and religious health (P>0.05). Conclusion: Considering the influence of religious culture in Yazd City, Iran, it is natural to expect religious influences to serve as a source of adaptation to society. Based on the results obtained and the higher mean spiritual health score of the students studied compared to similar studies, it would be appropriate to implement programs aimed at maintaining and promoting spiritual health.